A Novel Structure of High Voltage Gain DC‐DC Converters for Photovoltaic (PV) Applications - Farzad Karimian; Ali Nahavandi; Pouria Pakbaz (Engineering Reports)
ABSTRACT In this paper, a new structure of high‐voltage‐gain DC‐DC boost converters is proposed for photovoltaic applications. The proposed converter has high voltage gain and low voltage stress on switches and diodes, which is the main factor in reducing losses and increasing circuit efficiency. The switching elements of the circuit have a common ground with each other and with the output, making the control of the switching elements simpler. This converter can be fed from two input power sources in such a way that the output voltage of two separate solar panels can be converted to input and have a high voltage level at the output. Some of the diodes that are used in the proposed converter operate under zero voltage and zero current turning on and turning off, which reduces circuit losses. The proposed converter has two modes of operation. After analysis and calculations, the proposed converter is simulated using Matlab/Simulink. Finally, a laboratory prototype of the proposed converter is presented to verify its performance.